2014
DOI: 10.1037/a0033753
|View full text |Cite
|
Sign up to set email alerts
|

Components of working memory and visual selective attention.

Abstract: Load theory (Lavie, N., Hirst, A., De Fockert, J. W., & Viding, E. [2004]. Load theory of selective attention and cognitive control. Journal of Experimental Psychology: General, 133, 339-354.) proposes that control of attention depends on the amount and type of load that is imposed by current processing. Specifically, perceptual load should lead to efficient distractor rejection, whereas working memory load (dual-task coordination) should hinder distractor rejection. Studies support load theory's prediction th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 57 publications
(136 reference statements)
4
29
0
Order By: Relevance
“…WM tasks t ypically present increasingly complex sequences of information (words, letters, numbers, shapes, pictures, arrows, etc.) to participants and ask that they recall, reproduce, or use that information in the order it was presented to them (for some examples of WM tasks, see Burnham, Sabia and Langan 2013).…”
Section: Methodsmentioning
confidence: 99%
“…WM tasks t ypically present increasingly complex sequences of information (words, letters, numbers, shapes, pictures, arrows, etc.) to participants and ask that they recall, reproduce, or use that information in the order it was presented to them (for some examples of WM tasks, see Burnham, Sabia and Langan 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Although most studies of cognitive load have used verbal working memory tasks (e.g., remembering a series of numbers or letters), a recent study attempted to assess the effect of loading other working memory components (Burnham, Sabia, & Langan, 2014). For participants performing a visual search task (identifying a green diamond among five or nine green circles), loading the central executive (i.e., participants were given a starting number and had to complete a backwardcounting task for the duration of the trial), visual working memory (remembering four colored squares and indicating whether a probe color was present in the original set), and spatial working memory (remembering the locations of two squares and indicating whether two probe squares were in the same locations as the original set) increased distraction.…”
Section: Cognitive Loadmentioning
confidence: 99%
“…This study also observed that the effect was stronger when the irrelevant singleton overlapped with the WM load but only when difficult to verbalize pictures were used. A study of Burnham et al (2014) explicitly tested the role of different WM components in attentional capture. They found that only tasks that tax visuospatial WM and executive control increased distracter interference, while a phonological WM load did not affect capture.…”
Section: Working Memory and Visual Searchmentioning
confidence: 99%